Harmonic Current Elimination for Rectifiers Based on N Times Notch Filter and PR Controller - WANG Na; MU Yuanpeng (机车电传动)
For suppressing net-side low-order harmonics current, the mechanism and distribution of the harmonics were first derived. On the basis of theoretical analysis, a double closed loop harmonic suppression algorithms which combined N times notch filter and proportional-resonant (PR) controller was presented. The outer voltage loop control scheme based on N times notch filter can eliminate the DC-link voltage ripples without affecting the dynamic performance of the control system. The inner current loop control scheme based on PR controller with harmonic compensation can eliminate the steady-state error of AC signal, and further suppress the low-order harmonics in the line current, such as 3rd, 5th and 7th. Finally, the validity and effectiveness of the proposed scheme were verified with Matlab simulation and dSPACE+TMS320F2812 Hardware-in-the-Loop experiment results.